2022
DOI: 10.3389/fmicb.2022.830333
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dairy Cows Bedding Material on the Microbial Structure and Antibiotic Resistance Genes of Milk

Abstract: The presence of pathogenic bacteria and antibiotic resistance genes (ARGs) in milk are among the most important issues related to the safety of dairy products and the health of consumers. However, despite that dairy cow are housed for long periods of time on different beddings, the effect of different bedding materials on the microbiota and presence of ARGs is unclear. In this study, the composition of microorganisms, and the presence of mastitis pathogens and 33 ARGs targeting seven antibiotics in raw milk pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Related reagents to be used were MycoEasy rapid mycoplasma detection kit (Cellapy), TAE (50 ×) (Beyotime), Agarose (Biofroxx), DNA ladder (Beyotime), and GoodView Nucleic Acid Dye (SBS Genetech). The supernatant of cell culture will be collected, and follow the Mycoplasma Detection Kit operation manual for subsequent operations The positive standard for mycoplasma is about 280 BP, and the primer dimer was about 80 BP [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Related reagents to be used were MycoEasy rapid mycoplasma detection kit (Cellapy), TAE (50 ×) (Beyotime), Agarose (Biofroxx), DNA ladder (Beyotime), and GoodView Nucleic Acid Dye (SBS Genetech). The supernatant of cell culture will be collected, and follow the Mycoplasma Detection Kit operation manual for subsequent operations The positive standard for mycoplasma is about 280 BP, and the primer dimer was about 80 BP [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Note: The positive standard for mycoplasma is about 280 BP, and the primer dimer was about 80 BP. ( Wu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The harvested DP T lymphocytes were transferred to lymphoid differentiation material-coated plates, and 10 ng/mL IL-2, 10 ng/mL IL-15, and 6.25 µL human CD3/CD28/CD2 T cell activator were added to each well for 7–14 days for maturation and differentiation of CD8 + T cells ( Minagawa et al, 2018 ; Hu et al, 2020 ; Ji et al, 2022 ; Wu et al, 2022 ; Jian et al, 2023 ). Except for mature T cells, most immature lymphocytes, including CD4 + CD8 + DP T cells, died as a result of T cell receptor (TCR) rearrangement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These suggest that HGT may play a vital role in the spread of aminoglycoside-, β-lactamasand FCA-resistant genes in camel milk samples. More and more studies have reported that HGT is an important pathway for the transmission of ARGs, causing antibiotic-resistant bacteria to emerge in a variety of environments, as well as in raw milk [42,43].…”
Section: Transmission Of Args In Camel Milkmentioning
confidence: 99%